Physiological Assessment of Sex Hormones in Infected Women with Cutaneous Leishmania - Ali, Hanady Salih; Muhsen, Saria Naji; Muhsen, Senaa Naji (Journal for Research in Applied Sciences and Biotechnology, 2023)
The results of the clinical and laboratory examination showed 60 samples of women with cutaneous leishmaniasis in Salah Al-Din Governorate for the period from January to March 2022, during this research, the effect of skin leishmaniasis infection on the level of sex hormones (LH, Estrogen, Testosterone, FSH) was known, where the results were an increase in the level of LH, Estrogen, Testosterone, while the level of FSH hormone decreased in females compared to the control group.